From sounds to structures beyond the veil of Maya - Petrosino, Roberto; Cerrone, Pietro; Hulst, Harry van der (Studies in generative grammar ;, 2018)
"The term 'Maya' refers to our sensory perception of the world and to a superficial reality that we must look beyond to find the inner reality of things. Applied to the study of language, we perceive sounds, a superficial reality, and then we seek structures, the underlying reality in what we call phonology, morphology, and syntax. The papers collected in this volume reflect the research interests and influence of Andrea Calabrese"--